The phase of the de Haas-van Alphen oscillations, the Berry phase, and band-contact lines in metals: Электpонные свойства металлов и сплавов - Mikitik, G.P.; Sharlai, Yu.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We point out that measurements of a phase of the de Haas–van Alphen oscillations can give information on a degeneracy of electron-energy bands in a metal even though this degeneracy occurs far away from its Fermi level. As an illustration of this statement, the published experimental data on the de Haas–van Alphen effect in LaRhIn5, graphite, and zinc are discussed.